1978
DOI: 10.1126/science.705338
|View full text |Cite
|
Sign up to set email alerts
|

Changing Postdoctoral Career Patterns for Biomedical Scientists

Abstract: Between 1973 and 1977 the total number of Ph.D.'s holding postdoctoral appointments in the biomedical sciences increased at a rate of more than 550 individuals (12.5 percent) per year. During this same period the total number of doctorates awarded each year in these disciplines showed very little change. The postdoctoral growth can be attributed to substantial increases in both the numbers of recent graduates taking postdoctorals and the length of stay on these appointments. The lack of alternative employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Between 1973 and 1977 the number of biomedical PhD graduates holding post-doctoral appointments (traditionally fixed, short term contracts) increased at an annual rate of 12.5% (Coggeshall et al 1978). More recent research undertaken in the United States reported that non-tenure-track faculty now comprise some 75 percent of teaching staff at colleges and universities, including research institutions involved in granting biomedical doctorates (Check 2007;Howell et al 2010).…”
Section: The Impact(s) Of Academic Capitalisation On Funding Supervimentioning
confidence: 98%
“…Between 1973 and 1977 the number of biomedical PhD graduates holding post-doctoral appointments (traditionally fixed, short term contracts) increased at an annual rate of 12.5% (Coggeshall et al 1978). More recent research undertaken in the United States reported that non-tenure-track faculty now comprise some 75 percent of teaching staff at colleges and universities, including research institutions involved in granting biomedical doctorates (Check 2007;Howell et al 2010).…”
Section: The Impact(s) Of Academic Capitalisation On Funding Supervimentioning
confidence: 98%
“…This paper is a review of postdoctoral training programs in pediatric psychology. At a national level, the behavioral sciences are but one of the biomedical areas which have experienced an increase in both the number of postdoctoral training programs and the absolute numbers of students seeking and obtaining postdoctoral training (Coggeshall, Norvell, Bogorad, & Bock, 1978). In large part an outgrowth of expanded federal involvement in graduate and postgraduate education since the late 1950s, these areas have slowed in the amount of federal expenditures allocated to them as reconsideration is given to the potential needs for such personnel (Wohlford, 1978).…”
mentioning
confidence: 99%